PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (STUDI PADA PT. PG CANDI BARU SIDOARJO BAGIAN PRODUKSI) - ULFIATIN (Jurnal Ilmu Manajemen (JIM), 2017)
The purpose of this study to examine and test the effect of occupational safety and health behaviors on employee productivity at PT. PG Candi Baru part production. The approach used in this research is quantitative, where the population is 85 permanent employees and using saturated samples totaling 85 employees. Data analysis technique used is multiple linear regression with the help of software SPSS version 18. These results of the study simultaneously showed that the behavior of occupational safety and health impact on employee productivity. Then partially indicate that the safety variables have a significant positive effect on employee productivity, whereas occupational health variable didn’t effect on work productivity. Keywords: occupational safety, occupational health, and productivity of employees.